Enhancing Students' Conceptual Understanding of Hess's Law Through a Discovery Learning Model Integrated with a Simulator and Worksheets - Nopiyanti Nopiyanti; Gun Gun Gumilar; Heli Siti Halimatul Munawaroh; Ijang Rohman; Muhammad Nurul Hana; Miarti Khikmatun Nais (Universitas Negeri Gorontalo, 2026)
This study addresses the limited integration of Discovery Learning, a Hess’s Law Enthalpy Change Determination Simulator, and student worksheets (LKM). These components have generally been implemented separately or in different combinations in previous studies, and simulation-based learning in Hess’s Law remains limited. The study aimed to examine students’ conceptual understanding of Hess’s Law, both overall and across specific learning objectives, after implementing the Discovery Learning model integrated with a Hess’s Law Enthalpy Change Determination Simulator and student worksheets. The research employed a pre-experimental one-group pretest–posttest design involving 29 senior high school students. Data from the conceptual understanding test were analyzed using descriptive and inferential statistics. The paired-sample t-test revealed a statistically significant improvement from 35.06 to 63.22 (t= −8.11, p < 0.001). At the level of specific learning objectives, the Wilcoxon signed-rank test showed that students achieved greater gains in inferring Hess’s Law from comparisons of reaction pathways than in determining enthalpy change based on Hess’s Law. These findings indicate that the instructional approach was associated with improved conceptual understanding of Hess’s Law. This study suggests that integrating Discovery Learning with a Hess’s Law Enthalpy Change Determination Simulator and structured worksheets may support students’ conceptual understanding of Hess’s Law and serve as a practical instructional strategy in chemistry education.